1995
DOI: 10.1074/jbc.270.7.3442
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mitogen-activated Protein Kinase and Phosphatidylinositol 3′-Kinase Is Not Sufficient for the Hormonal Stimulation of Glucose Uptake, Lipogenesis, or Glycogen Synthesis in 3T3-L1 Adipocytes

Abstract: The precise mechanism by which insulin regulates glucose metabolism is not fully understood. However, it is known that insulin activates two enzymes, phosphatidylinositol 3'-kinase (PI 3'-K) and mitogen-activated protein kinase (MAPK), which may be involved in stimulating the metabolic effects of insulin. The role of these enzymes in glucose metabolism was examined by comparing the effects of insulin, platelet-derived growth factor (PDGF) and epidermal growth factor (EGF) in 3T3-L1 adipocytes. Treatment of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
125
2
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 58 publications
10
125
2
1
Order By: Relevance
“…Similar increases in protein content have been observed previously in WAT of obese VMH [3,12,27] and in Zucker rats [32]. Although the potential role of MAPK in the regulation of protein synthesis is controversial [31,[33][34][35], it cannot be excluded that the overexpression of MAPK in WAT of VMH rats could play a role in the general increase in protein content in adipocytes of obese rats. On the other hand, it has been shown in NIH3T3 fibroblasts that ERK-2 activation in vivo correlated with enhanced activation of RNA polymerase II [36,37].…”
Section: Discussionsupporting
confidence: 69%
“…Similar increases in protein content have been observed previously in WAT of obese VMH [3,12,27] and in Zucker rats [32]. Although the potential role of MAPK in the regulation of protein synthesis is controversial [31,[33][34][35], it cannot be excluded that the overexpression of MAPK in WAT of VMH rats could play a role in the general increase in protein content in adipocytes of obese rats. On the other hand, it has been shown in NIH3T3 fibroblasts that ERK-2 activation in vivo correlated with enhanced activation of RNA polymerase II [36,37].…”
Section: Discussionsupporting
confidence: 69%
“…However, the mechanism(s) by which the u-PAR gene is overexpressed is unclear at the present time. Since phorbol ester and a variety of growth factors including EGF, FGF, and vEGF, which up-regulate u-PAR synthesis, stimulate ERK activity (Zohn et al, 1995;Wiese et al, 1995;Bogoyevitch et al, 1994;Campbell et al, 1995;Jones et al, 1994;Lund et al, 1995), we undertook a study to determine the role of these MAPKs in regulating u-PAR expression in two cultured colon cancer cell lines. Several observations suggested a role for an ERK1-dependent signaling cascade in the regulation of u-PAR expression.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies on adipocyte function show that although insulin activates MAP kinase in 3T3-L1 adipocytes, insulin-dependent metabolic responses such as glucose uptake, glycogen synthesis, and lipogenesis are unaffected by the inhibition of MAP kinase with the MEK inhibitor PD98059 (29,30). In addition, the MEK inhibitor does not prevent or delay 3T3-L1 adipocyte differentiation (data not shown).…”
Section: Phosphorylation Of Ppar␥ By Map Kinase 10814mentioning
confidence: 97%
“…Moreover, recently Hu et al (28) demonstrated that the ectopic expression of a mutant PPAR␥2 (a serine to alanine mutation at position 112 in PPAR␥2, which is equivalent to Ser 82 of PPAR␥1) enhanced sensitivity to ligand-induced adipogenesis. These results strongly support the conclusion of the present paper.Additional studies on adipocyte function show that although insulin activates MAP kinase in 3T3-L1 adipocytes, insulin-dependent metabolic responses such as glucose uptake, glycogen synthesis, and lipogenesis are unaffected by the inhibition of MAP kinase with the MEK inhibitor PD98059 (29,30). In addition, the MEK inhibitor does not prevent or delay 3T3-L1 adipocyte differentiation (data not shown).…”
mentioning
confidence: 97%